2015
DOI: 10.4137/mri.s19794
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Efficacy of Gadobutrol for Contrast-enhanced Magnetic Resonance Imaging of the Central Nervous System: Results from a Multicenter, Double-blind, Randomized, Comparator Study

Abstract: PURPOSEContrast-enhanced magnetic resonance imaging (MRI) of the central nervous system (CNS) with gadolinium-based contrast agents (GBCAs) is standard of care for CNS imaging and diagnosis because of the visualization of lesions that cause blood–brain barrier breakdown. Gadobutrol is a macrocyclic GBCA with high concentration and high relaxivity. The objective of this study was to compare the safety and efficacy of gadobutrol 1.0 M vs unenhanced imaging and vs the approved macrocyclic agent gadoteridol 0.5 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 17 publications
(20 reference statements)
1
30
1
Order By: Relevance
“…A plethora of studies, including prospective head-to-head studies, have been performed on efficacy. For contrast-enhanced CNS, MRI publications of gadobutrol vs gadopentetate, 47 , 48 gadoterate, 49 and gadoteridol 50 , 51 are available. In all studies, certain efficacy parameters were superior to the comparators, be it conspicuity, 39 CNR, 40 overall preference and lesion contrast/enhancement, 49 or improved sensitivity and accuracy for detection of malignant lesions likely due to the high relaxivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of studies, including prospective head-to-head studies, have been performed on efficacy. For contrast-enhanced CNS, MRI publications of gadobutrol vs gadopentetate, 47 , 48 gadoterate, 49 and gadoteridol 50 , 51 are available. In all studies, certain efficacy parameters were superior to the comparators, be it conspicuity, 39 CNR, 40 overall preference and lesion contrast/enhancement, 49 or improved sensitivity and accuracy for detection of malignant lesions likely due to the high relaxivity.…”
Section: Discussionmentioning
confidence: 99%
“…They showed single dose of gadobutrol to be noninferior to a double dose of gadoteridol at detecting brain metastases. 50 Gutierrez et al 51 performed a phase 3 study with 390 patients concluding that gadobutrol demonstrates greater contrast enhancement and improved sensitivity and accuracy for detection of malignant disease than gadoteridol, likely because of its higher relaxivity.…”
Section: Efficacymentioning
confidence: 99%
“…5 That differences in r1 relaxivity reflect differences in diagnostic efficacy is borne out by evidence from numerous large-scale intraindividual crossover studies. [1][2][3][4][8][9][10][11] These studies have shown that differences in SI enhancement and imaging performance reflect differences in r1 relaxivity and that the magnitude of the differences in SI enhancement a Comparisons based on the number of patients with both postdose T1SE images assessed and technically adequate: n ϭ 96 for reader 1, n ϭ 94 for reader 2, and n ϭ 95 for reader 3. Numbers in parentheses, except where noted, represent proportions of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of enhancement was determined on the basis of a predefined 4-point scale: 0 (none), not visualized on 1 (or both) of the postcontrast sequences; 1 (subtle), faintly visualized on 3D sequences but better visualized on axial images (or vice versa); 2 (adequate), moderate degree of enhancement, equally seen in both 3D and axial sequences; and 3 (excellent), strong and sharply demarcated enhancement on both sequences. 20 Disagreements between readers were resolved by consensus review for presumed diagnoses and adjudicated by a third reader (P.S.) with 20 years of experience for the remaining variables.…”
Section: Individual Analysismentioning
confidence: 99%